The de novo transcriptome of workers head of the higher group termite Globitermes sulphureus Haviland (Blattodea: Termitidae). Issue 12 (December 2019) - Hussin, Nurul Akmar; Najimudin, Nazalan; Ab Majid, Abdul Hafiz
Abstract: The subterranean termite Globitermus sulphureus is an important Southeast Asian pest with limited genomic resources that causes damages to agriculture crops and building structures. Therefore, the main goal of this study was to survey the G. sulphureus transcriptome composition. Here, we performed de novo transcriptome for G. sulphureus workers' heads using Illumina HiSeq paired-end sequencing technology. A total of 88, 639, 408 clean reads were collected and assembled into 243, 057 transcripts and 193, 344 putative genes. The transcripts were annotated with the Trinotate pipeline. In total, 27, 061 transcripts were successfully annotated using BLASTX against the SwissProt database and 17, 816 genes were assigned to 47, 598 GO terms. We classified 14, 223 transcripts into COG classification, resulting in 25 groups of functional annotations. Next, a total of 12, 194 genes were matched in the KEGG pathway and 392 metabolic pathways were predicted based on the annotation. Moreover, we detected two endogenous cellulases in the sequences. The RT-qPCR analysis showed that there were significant differences in the expression levels of two genes β-glucosidase and endo-β-1, 4-glucanase between worker and soldier heads of G. sulphureus . This is the first study to characterize the complete head transcriptome of a higher termite G. sulphureus using a high-throughput sequencing. Our study may provide an overview and comprehensive molecular resource for comparative studies of the transcriptomics and genomics of termites. Abstract : Agricultural science; Animal science; Genetics; Transcriptomics; Globitermes sulphureus ; de novo transcriptome; Trinity; RNA-Seq; Gene expression; Cellulase.